2017
DOI: 10.1111/pcn.12554
|View full text |Cite
|
Sign up to set email alerts
|

Cancer screening participation in schizophrenic outpatients and the influence of their functional disability on the screening rate: A cross‐sectional study in Japan

Abstract: The findings demonstrated low rates of cancer screenings in schizophrenic patients in Japan. Our study suggests the need to encourage attendance at cancer screenings, especially in schizophrenic patients with severe symptoms/functional disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
4
32
0
Order By: Relevance
“…Our previous study found associations between social or physical factors and cancer screening non-participation in Japan (Fujiwara et al 2017). We found that symptom severity and functional disability related to schizophrenia were the most consistent risk factors for a lack of participation in screenings for all types of cancer.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Our previous study found associations between social or physical factors and cancer screening non-participation in Japan (Fujiwara et al 2017). We found that symptom severity and functional disability related to schizophrenia were the most consistent risk factors for a lack of participation in screenings for all types of cancer.…”
Section: Introductionmentioning
confidence: 68%
“…To the best of our knowledge, this is the first study to report local government record-based cancer screening rates among people with severe mental illness in Japan. Our previous study showed that the self-reported rates of cancer screenings among schizophrenic outpatients were 19.4%-30.8%, and that these rates were approximately onehalf those among the general population (Fujiwara et al 2017). These rates included any type of cancer screening, regardless of provider (municipal cancer screening, collective opportunistic cancer screening, and individual opportunistic screening).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations